Housing the family. Locating the single-family home in Germany. - (:unkn) unknown (Jovis, 2019)
Das Einfamilienhaus, seit den 1950er Jahren von der Politik gefördert, symbolisiert nach wie vor den Traum von Zuhause, Wohlstand und Status. Noch 2011 befanden sich in Deutschland zwei von drei Haushalten in einem Einfamilienhaus. Doch insbesondere im ländlichen Raum sind Kommunalverwaltungen und Lokalpolitik vermehrt mit leerstehenden Häusern aus den 1950er bis 1980er Jahren konfrontiert - und zugleich hält die Nachfrage vor allem junger Familien nach Neubaugrundstücken im Grünen an. Wohl wissend, dass Architektur und Stadtplanung dieses Wohn- und Lebensmodell längst kritisieren, werfen sie einen interessierten Blick auf das Einfamilienhaus zwischen Alltagsleben und Populärkultur, demografischem Wandel und Wohlfahrtsstaat, Materialaufwand und Ressourcenbilanz.

The suburban, detached single-family home is a major legacy of the Fordist decades of the twentieth century. In 2011, two-thirds of German households occupied such single-family houses. These buildings have embodied the political support for a way of life and type of living arrangement since the 1950s, and continue to symbolize dreams of home, prosperity, and social status. West German suburbs today consist mainly of single-family homes built between the 1950s and 1980s. However, municipal administrations and politics at the local level are now faced with the emptying of singlefamily housing areas at the edges of villages and small towns. At the same time, young families in particular are calling for building plots in the countryside. Whilst remaining aware of critiques of the single-family home in urban planning and architecture, this interdisciplinary volume offers fresh insights into this type of dwellings—from its place in everyday life and popular culture, to changing welfare regimes and demographic change, and to the implementation of ecological frameworks in the construction industry.
Keywords: Wohnform; Einfamilienhaus; Einfamilienhaussiedlung; Wohnwunsch; Familienwohnung; Eigenheimbau; Eigenheimsiedlung; Eigentumsförderung; Fertighaus; Fertighausindustrie; Denkmalschutz; Nachnutzung; Ökologische Erneuerung